DESIGN AN E-CATALOG ON INSTAGRAM USING CORELDRAW AS THE ADVERTISING - Arina Fatia Zahrah; Maskur (Universitas Islam Malang, 2023)
This research aims to provide complete information about Rumah Kinasih's products by developing E-Catalog as an advertising medium on Instagram. The research design used was Action Research. The research procedure consists of planning, action, observation, and reflection. Research data were collected through questionnaires distributed to 1 Owner, 2 marketing experts, 2 computer experts, 10 consumers, and 20 potential customers. The effectiveness of the design is measured using the EPIC Model (Emphaty, Persuasion, Impact, Communication). This is due to the attractive and creative design of the E-Catalog which provides detailed or information related to the products offered by Rumah Kinasih, Blitar Regency. The conclusion which could be inferred is that the E-Catalog product is very effective to be used as Instagram advertising media at Rumah Kinasih, Blitar Regency.